2019
DOI: 10.1021/acs.jpclett.9b00143
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Organometal Hybrid Perovskite Nanocrystals: Clarifying the Role of Oxygen by Single-Dot Photoluminescence

Abstract: Photostability has been a major issue for perovskite materials. Understanding the photodegradation mechanism and suppressing it are of central importance for applications. By investigating single-dot photoluminescence spectra and the lifetime of MAPbX 3 (MA = CH 3 NH 3 + , X = Br, I) nanocrystals with quantum confinement under different conditions, we identified two separate pathways in the photodegradation process. The first is the oxygen-assisted lightinduced etching process (photochemistry). The second is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…It was proven separately that OSTE acts as an effective oxygen barrier for the embedded nanoparticles. [ 13,26 ]…”
Section: Resultsmentioning
confidence: 99%
“…It was proven separately that OSTE acts as an effective oxygen barrier for the embedded nanoparticles. [ 13,26 ]…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, the crystallinity of the perovskite material increased and the film was adherent to the mesoporous TiO 2 . As demonstrated by timeresolved photoluminescence (PL) spectra, 104,105 the exciton lifetime in PEA-MAPbI 3 was much longer (40 ns) with respect to that in MAPbI 3 (12 ns). PEA-MAPbI 3 also exhibited a stronger absorption than MAPbI 3 in the range 350-800 nm, as shown in Fig.…”
Section: High-temperature Processed Front Electrodesmentioning
confidence: 99%
“…Furthermore, single NC PL spectroscopy data suggested that light illumination of MAPbX 3 NCs in oxygen-rich conditions resulted in a blue-shift of the PL maximum owing to the size reduction of NCs by light-induced NC surface etching. [150]…”
Section: Effect Of Light Irradiationmentioning
confidence: 99%